2002
DOI: 10.1002/mpo.1304
|View full text |Cite
|
Sign up to set email alerts
|

Body composition of long‐term survivors of acute lymphoblastic leukaemia†

Abstract: Female survivors of ALL are significantly fatter than those of other malignancies and healthy sibling controls. Caution should be observed in the application of published equations, derived from the normal population, for the calculation of body composition in children treated for ALL. The mechanism of onset of obesity remains unclear, but is probably multifactorial and related to previous cranial irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
1
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 33 publications
(41 reference statements)
2
69
1
3
Order By: Relevance
“…These survivors had completed treatment within 10 years at the time of study evaluation. 8,12,13,16,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Only 2 studies 14,40 examined BMI z score assessed $10 years after the completion of treatment (ie, off treatment $10 years). Because neither study reported SD/SE of the BMI z score, the meta-analysis did not include survivors who were off treatment beyond 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…These survivors had completed treatment within 10 years at the time of study evaluation. 8,12,13,16,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Only 2 studies 14,40 examined BMI z score assessed $10 years after the completion of treatment (ie, off treatment $10 years). Because neither study reported SD/SE of the BMI z score, the meta-analysis did not include survivors who were off treatment beyond 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are difficult to explain and are contradictory to those of van de Sluis et al (29), who found no difference in total body fat mass in patients who had not received CRT compared with controls 9.6 years after treatment. The majority of previous reports have studied cranially irradiated patients who have been found to have increased total body fat mass (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Body mass index (BMI) has been found to be significantly higher in female survivors when compared to both the expected norms, and control subjects. 29 Females treated with high dose cranial irradiation (20 -24Gy), at a young age were found to have a 55% chance of being overweight or obese in the future. 30 Male survivors also demonstrated higher BMIs indicating weight problems.…”
Section: -26mentioning
confidence: 99%
“…However, male control subjects also displayed signs of being overweight. 29 Therefore, the effect of cancer treatment on male survivors' body composition is not clear. In terms of bone mineral density (BMD), there were no differences between cases and controls, except regarding lumbar spine bone density, which was significantly lower in survivors.…”
Section: -26mentioning
confidence: 99%